Preparation of cement-based Al2O3-MgO-SiO2 sagger and its corrosion mechanism by cathode material during calcination. (15th August 2022) - Qian, Fan; Wang, Longguang; Ma, Weikui; Yu, Jianbin; Yang, Wengang; Liu, Guoqi; Zhang, Xin; Li, Hongxia
Abstract: Al2 O3 -MgO-SiO2 thin wall sagger bonded by CAS2 was prepared and then the corrosion test by cathode material was carried out. The results showed that Li2 CO3 diffused to the surface or interior of sagger in terms of liquid or gas phase and involved in the reaction, and the resultants were mainly LiAlO2, LiAlSiO4, CaO and MgO, Li2 O-Al2 O3 -SiO2 materials migrated to the original layer by driving force of dissolution-precipitation, while free CaO and MgO migrated to the precursor in terms of solid phase diffusion, therefore a loose working layer and a dense transition layer formed and led to large scale spalling. Highlights: Al2 O3 -MgO-SiO2 thin wall sagger bonded by CAS2 has excellent thermal shock resistance and corrosion resistance. Lithium source that reacts with sagger is Li2 CO3 in terms of liquid or gas phase, instead of Li2 O. Volume expansibility depends on reaction resultant, and LiAlSiO4 is the smallest than others, such as LiAlO2 and Li2 SiO3 . Li2 O-Al2 O3 -SiO2 and CaO-MgO migrate in opposite direction by dissolution-precipitation and solid diffusion respectively.